PD Iterative Self-learning Control for 3R Plane Robot Trajectory Tracking - Hongwei Gao; Kun Hong; Jinguo Liu; Yuquan Leng; Chuanyin Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to improve the speed and accuracy of the trajectory tracking control for 3R plane robot, a PD iterative self-learning control algorithm is proposed based on the PD iterative control algorithm. The error of target value and the actual value of this iteration is introduced into the PD learning gain to make the PD learning gain becomes a function of the error and to achieve the effect of self-learning. Simulation analysis of planar 3-link robot trajectory control shows that the proposed algorithm is better than unmodified in speed ability and accuracy. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3427